PENGGUNAAN LAT (LOWEST ASTRONOMICAL TIDE) UNTUKMENGGANTIKANMLWS (MEAN LOWWATER SPRINGS) SEBAGAI DATUMVERTIKAL BATAS LAUT INDONESIA - Adi Wijaya, Riko
Based on UNCLOS III Article 16, Indonesia as one of the coastal and archipelages is obliged to officially announce and submit a copy of the sealine map on an adequate scale or in the form of geographical coordinates to the Secretary General of the United Nations. Indonesia has submitted ocean boundaries via Government Regulation Number 38 of 2002 concerning a list of geographical coordinates of the Indonesian archipelago's base points and changes to Government Regulation Number 37 of 2008. In the regulation it was stated that Indonesia used the Mean Low Water Springs (MLWS) as a national datum vertical sea boundary. While IHO internationally recommends the use of Lowest Astronomical Tide (LAT). In determining the value of the LAT analysis of the tidal component and the prediction is based on the BIG’s tidal observation data. The value of the tidal component is determined by the least squares method. The results of the tidal component analysis were used for predictions for 19 years. While the MLWS value is obtained from Pushidrosal. The difference between these two values can determine the position of LAT against MLWS. Based on this research obtained the result that the position of the LAT under MLWS is 35%, the same as MLWS of 30%, and the LAT positions above MLWS is 35%, of a total 37 tidal stations with the same location between BIG and Pushidrosal data.With this study, it is expected that recommendation use of LAT as a vertical datum for sea bounds replaces MLWS for the determination of more optimal Indonesian sea boundaries can be utilized.